CYP2A6*4 allele gene high frequency associated with low-density lipoprotein cholesterol (LDL-C) among Javanese Indonesian smokers - Preiffer Agus Prasojo; Christine Patramurti (Pharmaciana, 2021)
The CYP2A6 gene, which codes the CYP2A6 enzyme, has known to have ahigh polymorphism. This polymorphism could decrease, increase, or eliminate the CYP2A6 enzyme activity. CYP2A6*4, an inactive allele, decreased the CYP2A6 enzyme activity. One of the CYP2A6 enzyme-specific substrates is nicotine. This inactive allele could decrease nicotine metabolism that causes high nicotine levels in the blood. In addition, it caused the increasing levels of Low-Density Lipoprotein Cholesterol (LDL-C) by expanding the lipolysis process. The purpose of this research was to evaluate the effect of the CYP2A6*4 allele gene on LDL-C levels. Respondents in this study were 31 male Javanese smokers. This research is an analytic observational study with a cross-sectional design. Polymerase chain reaction (PCR) methods use to identification the CYP2A6*4 allele gene. This study shows that a high-frequency CYP2A6*4 alleles gene among the subject was detected, with an allele frequency is 93.55%. Furthermore, this CYP2A6*4 allele gene did not impact LDL-C levels, with the Odd Ratio value was 1.636 (P-Value = 0.737). In conclusion, the CYP2A6*4 allele gene does not significantly affect the LDL-C levels in Javanese Indonesian smokers.